Implementasi Media Visual Animasi Dalam Meningkatkan Keterampilan Menulis Teks Eksposisi Di Sekolah Menengah Pertama - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
Expository text writing is an essential skill in Indonesian language education at the junior high school level. However, students’ writing performance in expository texts remains relatively low, particularly in the aspects of idea organization, clarity of arguments, and proper language use. This literature study aims to explore the implementation of visual animation media as a learning tool to enhance students’ skills in writing expository texts. This research employs a qualitative descriptive approach through a literature review of various national and international journals published between 2020 and 2025. The findings indicate that visual animation media can increase students’ learning motivation, facilitate understanding of text structure, and assist students in developing ideas logically and coherently. Furthermore, animation effectively establishes connections between the topic and real-life contexts, thereby strengthening students’ arguments in expository writing. The use of interactive animations incorporating narrative, visual, and audio elements creates a more engaging and communicative learning environment. This study recommends integrating animation media into expository writing instruction as part of innovative, technology-based teaching strategies. It is expected that these findings will contribute to improving the quality of writing instruction in junior high schools more effectively and enjoyably.